(untitled) (Research, Society and Development, 2020)
The aim of the study is to build a manual of standards and routines for the immunization room. Methodological research, conducted in October to December 2019 and focused on the development of a tool that can be used as a form of permanent health education by the team working inside the immunization room. For this, four steps were performed: bibliographic survey, content selection, textual elaboration and diagramming. The study resulted in the elaboration of a manual entitled "Manual of Norms and Routines for the Immunization Room", which highlights themes about the team of the vaccine room, reception, hand hygiene, cold chamber, immunobiological stability, room organization, printed and manuals used within the sector, vaccination calendar 2019/2020, vaccine contraindications, post-vaccination adverse events, human rabies prophylaxis, special immunobiological center, post-vaccination care and references used for the construction of the manual. It is noteworthy that because it is a low-cost tool, it is expected that this study can assist in the correct practice in the administration and management of vaccine rooms.